A Comparison of Characterization and Moral Values in Cinderella and Bawang Merah Dan Bawang Putih Fairy Tales: A Comparative Literature Study - Sijabat, Asnita br (Peneliti.net, 2023)
In this research, the researcher intends to examine the character and moral values in the fairy tales Cinderella and Bawang Merah Bawang Putih as a comparison. Comparison is intended to find similarities and differences in the two fairy tales. The two fairy tales were chosen because the stories have similarities and differences. The two fairy tales can be compared because they have the same theme, namely injustice. This type of research is qualitative descriptive research. Research Target/Subject This research is library research. The research material is two fairy tale literary works entitled